Peran Asam Lemak Omega-3 pada Dislipidemia dan Penyakit Kardiovaskular - Grace Fonda; Raymond Pranata; Hadrian Deka (Jurnal Kardiologi Indonesia, 2016)
Globally, coronary heart disease (CHD) is a leading cause of mortality and morbidity, especially in developing countries. Both marine and plants sources of omega-3 fatty acids has been shown to be beneficial in reducing CHD mortality. Beside of anti-arrhythmic effects, omega-3 has been shown anti-thrombotic and anti-atherosclerotic effect. In 2011, US population spent about 25 billion US dollar for omega-3 supplement; it is projected to be 35 billion US dollar in the year 2016. Several reviews on randomized controlled trial conclude that omega-3 fatty acids reduced plasma triglyceride level consistently in a dose-dependent fashion. Other beneficial effects on blood pressure, endothelial function and high density lipoprotein (HDL) level participate in lowering CHD mortality. American Heart Association (AHA) recommended routine fish consumption as secondary prevention in patient at risk. Omega-3 fatty acids role in primary prevention is inconclusive and need further investigation regarding cost-benefit and bleeding risk.